Thailand : Building Partnerships for Environmental and Natural Resources Management - World Bank (Washington, DC, 2013)
This Strategy Note sets out a framework for World Bank involvement in the environment sector in the immediate to medium term. It elaborates upon and reinforces the environmental objectives specified in Thailand's Eighth National Economic and Social Development Plan (1997-2001) and the World Bank's Country Assistance Strategy for 1998. This report is organized in six sections. Section 1 provides a brief introduction to the changing economic and environmental context, and Section 2 describes the policy and institutional framework in Thailand. Section 3 analyzes environmental trends and priorities in the green, blue, and brown agendas. Section 4 presents emerging challenges and the approach used in setting priorities for World Bank involvement. Section 5 describes a proposed environmental strategy that includes potential World Bank operations. Lastly, Section 6 offers a framework for benchmarking progress.